Characteristics of registered clinical trials assessing strategies of medication errors prevention. An unusual cross sectional analysis - Giannetta, Noemi; Dionisi, Sara; Villa, Giulia; Cappadona, Rosaria; Fabbian, Fabio; De Giorgi, Alfredo; Manara, Duilio Fiorenzo; Di Muzio, Marco; Manfredini, Roberto; Di Simone, Emanuele (Acta Biomedica Atenei Parmensis, 2021)
Background: ClinicalTrials.gov is the oldest and largest of these registries. Through this, the researchers can explore and monitor the clinical research landscape. In the last decades, the number of Medline-indexed publications on adverse events and medication errors have increased exponentially. The aims were to define the prevalence of clinical trials that have as outcome the medication errors and to describe the characteristics of these trials, including their distribution across countries, and publication rate. Methods: A cross-sectional analysis of all clinical trials reporting as primary outcome medication errors identified through ClincialTrials.gov. Results: Among 5.881 trials, only 1,68% focused on intervention to improve medication safety process and prevent medication errors. 25,3% of clinical trials included had their primary outcome changed (p= ,005). Recording study results in ClinicalTrials.gov was associated with trials that had their primary outcome changed (OR: ,060; 95% C.I.: ,007 – ,541). Only few interventional trials were totally compliant with the ICMJE policy. For all trials completed in our sample, in mean 7,44 months (median: 12 months) elapsed between study completion and the first publication in Medline showing the trial’s identification number. Conclusions: This study demonstrates several strengths of using ClinicalTrials.gov to track intervention to improve medication safety process. It is unknown how many trials are designed to focus on medication errors. However, 1,68% of trials focused on intervention to improve medication safety process.